Research of the New Generation Marine Navigation Security Communication System - Qian, Jingyi; Zeng, Huilu; Yao, Guowei; Kong, Fanwei (Transactions on Computer Science and Intelligent Systems Research, 2023)
With the number of Chinese ships rapidly increasing, the available channels for the Automatic Identification System (AIS) are serious congested. This has led to a sharp rise in collision warnings. The maritime communication System is comprehensively updated from AIS to VHF Data Exchange System (VDES) in order to ensure efficient communication of huge scale, high density maritime ships as well as guarantee marine navigation security. In this paper, the new generation marine navigation security communication system based on VDES is studied. Designing communication systems for ships at sea, shore-based base stations and space-based satellites; The two-way data exchange between huge scale, high density ships-to-ships and ship-to-shore by VHF frequency band in nearshore and port areas can promote the development of maritime navigation technology and maritime economic.